Corporate Governance in Microfinance Institutions - Di Benedetta, Pasquale (World Bank, Washington, DC, 2015)
This paper is organized as follows: this introduction is followed by a primer on the industry and on the evolution of the microfinance sector. The authors then examine the structure of the microfinance industry, (a) NGOs, cooperatives and credit unions, and commercialized vehicles; how they differ and why corporate governance differs according to the nature of the MFI; and (b) large networks, investment and bank-holding groups, and social services/faith-based groups. The authors then consider how corporate governance evolves and develops in MFIs as their structure and ownership changes. This is followed by an examination of the recurring issues and growing risks in the microfinance industry. The authors conclude with a look at the responses of governments, investors, and the industry itself to these issues and risks and propose some next steps.